Pengaruh Latihan Kardio terhadap Peningkatan VO2MAX - Karimah, Dhifa (Asosiasi Program Studi Olahraga PGRI Indonesia (APOPI), 2022)
Vo2max is the maximum level of oxygen during exercise. Oxygen is the most important part in the respiratory process, when oxygen is inhaled, the lungs will absorb and convert it into energy called Adenosine Triphosphate (ATP). This type of research is a descriptive qualitative narrative. This research is descriptive, describing something as it is, meaning that the data collected is in the form of words or reasoning, pictures, and not numbers. From the conclusion of the analysis, it shows that some cardio exercises are quite significant in increasing Vo2max, cardio exercises such as fartlek exercises are very significant, it can be proven by several studies, one of which is the Yudhi Kharisma study in 2020 as many as 24 treatments in 8 weeks with an intensity of 3 times a week can increase the average value of Vo2max is 8.27. Likewise with Didi Yudha Pranata's research in 2020 as many as 16 treatments can increase the average Vo2max value by 6.21.